2013
DOI: 10.1371/journal.ppat.1003527
|View full text |Cite
|
Sign up to set email alerts
|

The Late Endosomal HOPS Complex Anchors Active G-Protein Signaling Essential for Pathogenesis in Magnaporthe oryzae

Abstract: In Magnaporthe oryzae, the causal ascomycete of the devastating rice blast disease, the conidial germ tube tip must sense and respond to a wide array of requisite cues from the host in order to switch from polarized to isotropic growth, ultimately forming the dome-shaped infection cell known as the appressorium. Although the role for G-protein mediated Cyclic AMP signaling in appressorium formation was first identified almost two decades ago, little is known about the spatio-temporal dynamics of the cascade an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 81 publications
(109 reference statements)
5
72
0
Order By: Relevance
“…The various signaling components then interact within the endosomal compartments for sustaining signaling [13]. Endosomal compartments contain early and late endosomes.…”
Section: Introductionmentioning
confidence: 99%
“…The various signaling components then interact within the endosomal compartments for sustaining signaling [13]. Endosomal compartments contain early and late endosomes.…”
Section: Introductionmentioning
confidence: 99%
“…In yeast, the localization of Snx41 to endosomes is dependent on phosphatidylinositol‐3‐kinase (PI3K) activity (Hettema et al ., ). To determine whether the association of FgSnx41 with the endosomal membrane also requires PI3K activity, we treated freshly harvested conidia with the PI3K‐specific inhibitor LY294002 (Ramanujam et al ., ), and found that FgSnx41‐GFP was neither in punctate form nor EE localized; rather, it appeared diffused in the cytosol, with very faint fluorescence (Fig. b).…”
Section: Resultsmentioning
confidence: 95%
“…In the incipient appressorium, some punctuate structures (GFP signal) were observed in the conidium, germ tube and appressoria. This localization pattern was the same as the G‐protein signaling mediated by regulator of G‐protein signalling‐1 ( Rgs1 ) in M. oryzae (Ramanujam et al ., ). In the mature appressorium, the GFP signal was mainly centralized in the form of large punctuate structures in the appressorium (Fig.…”
Section: Resultsmentioning
confidence: 97%